THE INFLUENCE OF USING GROUP WORK AND READING ATTITUDE TOWARDS READING COMPREHENSION ACHIEVEMENT - Sunaryo (UNMUH BABEL PRESS, 2020)
This study was to investigate the influence of using group work and reading attitude towards the eleventh grade students’ reading comprehension achievement on narrative text. The population of this study was the eleventh grade students at Senior High School Puspita Air Kumbang. The sample was 60 students taken by using cluster random sampling. In carrying out of the research, the writer used an experimental method; factorial design. The writer distributed pretest, posttest, and attitude questionnaire in collecting the data. Then, in analyzing the data the writer used t-test and two-way ANOVA. The result of this study analysis indicated that; first, there was significant influence of group work technique towards the eleventh grade students’ reading comprehension achievement between those who had positive attitude and those who had negative attitude. Second, there was significant influence of conventional teaching technique towards the eleventh grade students’ reading comprehension achievement between those who have positive attitude and those who have negative attitude. Third, there was significant influence of group work technique and conventional teaching technique towards the eleventh grade students’ reading comprehension achievement between those who have positive attitude and those who have negative attitude. Forth, there is significant interaction effect of group work technique and reading attitude towards the eleventh grade students’ reading comprehension achievement between those who have positive attitude and those who have negative attitude.